Estimation of hydrological vulnerability in river basins of Argentinean plains. Issue 4 (2nd October 2021) - Bohn, Vanesa Y.; Piccolo, M. Cintia
ABSTRACT: Flooding, economic losses in agricultural activity and climatological variability are very natural phenomena on plains. In particular, the central plains in Argentina, that are the most productive agrarian areas in the country, are characterized by significant alternate inter-annual droughts and floods. Moreover, the topographic features of the study area contribute to high exposure to flooding. In this study, a method for estimating the Hydrological Vulnerability (HV), related to the hydrological surplus, is developed for three river basins in the Pampas plains in Argentina, which includes a comprehensive analysis and scoring of various physical, climatological and hydrological variables. All the data were processed in a raster format, in a GIS environment. Finally, the method was validated, in a qualitative and a quantitative form, with a world and national disasters database, government national and satellite data and previous studies. It provides a structured approach for carrying out an assessment of hydrological vulnerability, which is applicable at different spatial scales.